Exposure to known COVID-19 infection risk factors among healthcare workers responding to COVID-19 outbreak in Lagos State, Nigeria-2020 - Olugbenga Odukanmi; Muhammed Balogun; Olayinka Ilesanmi; Bisola Adebayo; Adetunji Adenekan; Oluwatosin Onasanya; Oyeladun Okunromade; Ugochukwu Madubueze; Chukwuma Umeokonkwo; Patrick Nguku (Journal of Interventional Epidemiology and Public Health)
Introduction: Globally, over 790,000 deaths of COVID-19 cases were reported by August 20, 2020, these numbers included healthcare workers (HCW). The high infection rate among HCW to COVID-19 is worrisome requiring countries to protect them. We examined the risk of exposure among HCW.